Latin American nationalism : identity in a globalizing world - Siekmeier, James F. (New approaches to international history., 2017)
With ethnic and class-based national movements taking center stage in countries like Bolivia and Venezuela, nationalism has proven to be one of the most durable and important movements in Latin America. In understanding the history of these nationalisms, we can understand how Latin America relates to the rest of the world. As Latin America inserts itself into a rapidly globalizing world, understanding the changing nature of national identify and nationalism is key. By tracing the important historical origins of present-day Latin American nationalism, this book gives readers a thorough introduction to the subject. Only by understanding how nationalism came to be such an important social and political force, can we understand its significance of today. In turn, understanding Latin American nationalism helps us understand how Latin America shapes, and is shaped by, a rapidly globalizing world.